Low-Cost And Portable Interactive Sinusoidal Digital Signal Generator By Using FPGA - Jidin, Aiman Zakwan; Mahzan, Irna Nadira; Hassim, Nurulhalim; Kadmin, Ahmad Fauzan (Penerbit Universiti, UTeM, 2018)
This paper presents the development of a low-cost and portable interactive Sinusoidal signal generator which has been implemented on FPGA device. The sine wave is generated by using a Lookup Table method, where the sine values are precalculated and stored in the onboard memory. The frequency of the generated signal is modified by changing the value of the memory address incremental step. In addition, the implemented signal generator is serially connected to a graphical user interface (GUI) on a PC, which can be used to select the type of the desired signal to be generated and to set the signal frequency. The proposed design was successfully implemented in ALTERA Cyclone II DE0 FPGA Development Board, where the sine wave can be generated within the range of 1 kHz to 1 MHz, with 1 kHz frequency resolution.